An improved 2-OPT optimisation scheme for Hamilton loop. (30th November 2020) - Bo, Sun; Shicai, Lu; Yongquan, You; Chuanxiang, Ren
Aiming at the problem that the traditional traffic route planning has a single target strategy and cannot be adjusted according to the actual situation, a multi-lane planning model based on Hamilton loops is proposed, which uses the characteristics of Hamilton loops to cover all nodes in the set and uses the nearest neighbour algorithm to obtain the initial loop. The improved 2-OPT algorithm avoids the problem caused by randomness and improves the efficiency of 2-OPT algorithm. In the case of considering road congestion, the introduction of speed parameters and comprehensive influence factors can give different path planning schemes according to different actual situations, and find the shortest time path and the shortest path, which makes Hamilton loop model more practical. The simulation results verify that the improved model can meet different planning requirements, achieve more targeted path planning, optimise the path planning scheme, and enhance people's travel efficiency.